2023
DOI: 10.1093/jsxmed/qdac029
|View full text |Cite
|
Sign up to set email alerts
|

Children and adolescents in the Amsterdam Cohort of Gender Dysphoria: trends in diagnostic- and treatment trajectories during the first 20 years of the Dutch Protocol

Abstract: Background Twenty years ago, the Dutch Protocol—consisting of a gonadotropin-releasing hormone agonist (GnRHa) to halt puberty and subsequent gender-affirming hormones (GAHs)—was implemented to treat adolescents with gender dysphoria. Aim To study trends in trajectories in children and adolescents who were referred for evaluation of gender dysphoria and/or treated following the Dutch Protocol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…There was evidence from multiple mainly pre-post studies that puberty suppression exerts its expected physiological effect, as previously demonstrated in children with precocious puberty 73. In adolescents experiencing gender dysphoria/incongruence, puberty suppression is initiated at different stages of puberty,74 and two studies found that the effects on secondary sex characteristics may vary depending on whether treatment is initiated in early puberty versus mid-puberty, with potentially different outcomes for birth-registered males and females 30 35. Multiple studies also found that bone density is compromised during puberty suppression, and gains in height may lag behind that seen in other adolescents.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…There was evidence from multiple mainly pre-post studies that puberty suppression exerts its expected physiological effect, as previously demonstrated in children with precocious puberty 73. In adolescents experiencing gender dysphoria/incongruence, puberty suppression is initiated at different stages of puberty,74 and two studies found that the effects on secondary sex characteristics may vary depending on whether treatment is initiated in early puberty versus mid-puberty, with potentially different outcomes for birth-registered males and females 30 35. Multiple studies also found that bone density is compromised during puberty suppression, and gains in height may lag behind that seen in other adolescents.…”
Section: Discussionmentioning
confidence: 81%
“…Many studies reported effects of both puberty suppressants and hormones used in later adolescence for feminisation/masculinisation. In adolescents, GnRH-a often continues during hormone treatment,74 or for adolescents who do not receive puberty suppression, GnRH-a or other anti-androgens may be offered at initiation of hormones 66. This makes long-term follow-up of puberty suppression difficult to assess, including any differences between the types of interventions that are offered and when these are initiated, and the few studies reporting long-term outcomes either did not control for this or reported overall effects for both interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, guidelines have broadened these criteria, for example, removing minimum age4 7 8 and making changes to the requirement of a diagnosis of gender dysphoria (Diagnostic and Statistical Manual of Mental Disorders 5th edition, DSM-5), being replaced by gender incongruence (International Classification of Diseases 11th revision, ICD-11) 3. In a study of 1766 children and adolescents receiving care at a national gender service in the Netherlands (1997–2018), 202 birth-registered males and 454 birth-registered females received hormones at a median age of 16.0 (IQR 15.5–17.1) and 16.7 (16.0–17.5), respectively 9. In the UK, the mean age of consent for treatment was 17.3 (SD 0.1) 10…”
Section: Introductionmentioning
confidence: 99%